Case Report: Thymoma-associated myasthenia gravis, myositis, myocarditis, and anti-GAD65 autoimmune encephalitis: a unique case of paraneoplastic polyautoimmunity - Leiva-Murillo, Enmanuel A.; Martínez-Hernández, Eugenia; Aldecoa, Iban; Castro, Pedro; Richart, Valeria; Milisenda, José C.; Matas-García, Ana (Frontiers in Immunology, 2026)
Neurological and autoimmune muscle comorbidities are rare in thymoma-associated myasthenia gravis (TAMG). The incidence of myositis is likely underestimated due to its clinical similarity. Few cases of autoimmune encephalitis (AE) have been reported in TAMG, most of which are associated with neuronal surface antibodies. We present the case of a 41-year-old woman with weakness and bulbar dysfunction, and elevated muscle and cardiac enzyme levels, who developed seizures and a decreased level of consciousness. Among the complementary tests, electromyography revealed a postsynaptic neuromuscular junction disorder. Muscle biopsy revealed inflammatory myopathy (IM), and cardiac magnetic resonance imaging (MRI) showed myocardial edema. Electroencephalography showed epileptiform activity, while brain MRI revealed bilateral T2/FLAIR hyperintensities in the medial temporal lobe. Neuroimmunological studies detected anti-acetylcholine receptor and anti-glutamic acid decarboxylase 65 (anti-GAD65) antibodies. Chest computed tomography (CT) revealed a mediastinal mass, which was later confirmed as a thymoma. The patient received corticosteroids, intravenous immunoglobulin, plasma exchanges, and rituximab. The simultaneous coexistence of myasthenia, myositis, myocarditis, and AE in a patient with thymoma has not been previously described in the medical literature. The presence of anti-GAD65 in this context is exceptional. In this case, early recognition and aggressive treatment led to a remarkable recovery. Clinicians should maintain a high index of suspicion for the coexistence of autoimmune disorders in patients with TAMG. IM may indicate a more serious disease, and myocarditis can be life-threatening. Neurological signs, such as memory loss, confusion, and seizures, may indicate the development of AE.